Development of a novel system to quantify the spatial–temporal parameters for crutch-assisted quadrupedal gait. (17th January 2017) - Yozu, Arito; Hamada, Masashi; Sasaki, Takuya; Tokushige, Shin-ichi; Tsuji, Shoji; Haga, Nobuhiko
Abstract: Patients with gait disorders often use bilateral crutches along with their own two legs. It is a kind of quadrupedalism. Crutch-assisted gait is usually described and evaluated qualitatively. In this study, we developed a system to quantify the spatial and temporal parameters for crutch-assisted quadrupedalism. Our system consists of walkway hardware and our originally developed software. We specifically extended the measurable area to 1200 mm × 4800 mm, large enough to measure crutch gait. Using our system, we could describe crutch gait precisely. Our system has a capability to evaluate differences between patients and changes within a patient. Abstract :